Regio- and Diastereoselective Synthesis of Novel Polycyclic Pyrrolo[2,1-a]isoquinolines Bearing Indeno[1,2-b]quinoxaline Moieties by a Three-Component [3+2]-Cycloaddition Reaction - Moghaddam, Firouz Matloubi; Moafi, Atiyeh; Jafari, Behzad; Vilinger, Alexander; Langer, Peter (Synlett, 2020)
A regio- and diastereoselective synthesis of 2,3-dihydro-10b′H-spiro[indeno[1,2-b]quinoxaline-11,1′-pyrrolo[2,1-a]isoquinoline]-2′,3′-diylbis(phenylmethanone) derivatives containing four contiguous chiral stereocenters was achieved through 1,3-dipolar cycloaddition of isoquinolinium N-ylides in a one-pot three-component reaction. The desired products were obtained in short reaction times and in moderate to high yields (up to 92%) under relatively mild reaction conditions. The structure and relative stereochemistry of the desired product was confirmed by X-ray diffraction analysis.
Keywords: pyrroloisoquinolines; indenoquinoxalines; spiro compounds; diastereoselectivity; 1,3-dipolar cycloaddition; multicomponent reaction